2010
DOI: 10.4049/jimmunol.0903802
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Receptor Coactivator 3 Is Required for Clearing Bacteria and Repressing Inflammatory Response in Escherichia coli-Induced Septic Peritonitis

Abstract: Steroid receptor coactivator 3 (SRC-3) is a multifunctional protein that plays an important role in regulation of bacterial lipopolysaccharide-induced inflammation. However, its involvement in host defense against bacterial infection remains unclear. Herein we used SRC-3 knockout mice to assess the role of SRC-3 in antibacterial defense in E. coli-induced septic peritonitis. After E. coli bacteria were injected intraperitoneally, SRC-3 deficient mice exhibited excessive local and systemic inflammatory response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 53 publications
2
28
0
1
Order By: Relevance
“…Recently, we reported that SRC‐3/AIB1‐deficient macrophages exhibit increased ROS levels and a concomitant reduced expression of Bcl‐2,10 and it has been reported that ROS can suppress the expression of Bcl‐2 11. Therefore, we examined whether the levels of ROS in CCA cells is affected by AIB1.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, we reported that SRC‐3/AIB1‐deficient macrophages exhibit increased ROS levels and a concomitant reduced expression of Bcl‐2,10 and it has been reported that ROS can suppress the expression of Bcl‐2 11. Therefore, we examined whether the levels of ROS in CCA cells is affected by AIB1.…”
Section: Resultsmentioning
confidence: 98%
“…We previously reported that SRC-3 −/− mice exhibited more susceptible to E. coli -induced septic peritonitis due to an uncontrolled overwhelming inflammation and a defect in bacterial clearance (20). The defect in bacterial clearance is at least in part due to the decreased E. coli phagocytosis by SRC-3 −/− macrophages and increased SRC-3 −/− macrophage apoptosis, indicating that SRC-3 exerts its anti-bacterial function by enhancing bacterial phagocytosis and macrophage survival during peritoneal E. coli infection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this study, our previous study demonstrated that SRC-3 −/− mice produced significantly more proinflammatory cytokines and macrophage SRC-3 could inhibit cytokine mRNA translation in response to LPS challenge (19), indicating that macrophage SRC-3 can protect mice by regulating proinflammatory cytokine balance in LPS-induced endotoxic shock. We also reported that SRC-3 −/− mice were more susceptible to Escherichia coli -induced septic peritonitis due to an uncontrolled overwhelming inflammation and a defect in bacterial clearance (20), suggesting a critical protective role for SRC-3 in the host defense against bacterial infection. However, its involvement in host defense against A/E enteric bacterial pathogen remains poorly defined.…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, loss of NCOA3 resulted in derepression of translation of such proinflammatory transcripts leading to uncontrolled cytokine production. Another study demonstrated that paradoxically, NCOA3 KO mice are defective in bacterial clearance despite heightened TNF, IL6 and IL1␤ expression in peritoneal fluid following E. coli-induced peritonitis (104). Indeed, NCOA3 KO macrophages exhibited decreased expression of SR-A protein that aids in Fc-independent phagocytosis of microorganisms leading to bacterial dissemination and sepsis.…”
Section: Nontranscriptional Effects Of Ncoasmentioning
confidence: 99%